Geographical location, Personal Preferences and identities of the tourist and their role in the Digital Marketing industry for Touristic Destination at Al Hijr Center - Alanazi, Bader Nayil Muflih; Al-Faqeer, Bader Adil (Al-Adab Journal, 2021)
Al Hijr considers one of most important touristic sites within Kingdom of Saudi Arabia. Despite entering on the list of United Nations Educational, Scientific and Cultural Organization (UNESCO) for world heritage locations, but the data and information of archaeological site are still showing the traditional marketing and media methods and consider as general information, so it needs more time to assess its efficacy and accuracy. The study aims to create E- program for touristic marketing at Al Hijr center, which depending on touristic geographic database for study region, tourist`s personal characteristics, making sure of role the information to show with the proper results. The researcher has used the inductive methodology according to procedures required to solve the problem of study. The findings of study conclude that the significance of caring with the information and data for geographic touristic and descriptive attraction sites, and its role on decreasing the difficulties, which may be faced the tourist, its enabling with E- programs to carry out the task of touristic marketing, enabling the tourist to reach at many of alternative touristic sites, prioritizing of tourist , and setting up touristic alternative automatically according to the personal characteristics and interests. The study recommends that the significance of increasing the investment on modern techniques, expanding on E- marketing for touristic destinations, and the necessity of caring with information and data, and building the specialized centers for caring with these data and working to educate the workers on the field of tourism with its value and significance.